Modernization of the Kalmyk and Mongolian societies at the turn of the 20th and 21st centuries: social aspects - Namrueva, Lyudmila V. (The New Research of Tuva, 2013)
Article is devoted to modernization features in the social sphere of Mongolian and Kalmyk societies. The changes in the systems of education and healthcare are shown on the basis of statistical data and the secondary analysis.